Reentry as Experienced by Women in Jail: Advocating for Change. Issue 1 (3rd April 2021) - Dobmeier, Robert A.; Korni, Swaroop Kumar; Brown‐Smythe, Claudette; Outland, Rafael L.; Williams‐McGahee, Patricia; LaDelfa, Anna N.; White, Joanna
Abstract : We conducted a phenomenological study with 35 women in a substance abuse treatment jail program about their lived experiences in preparing for reentry. The women addressed their past, the needs of their families, and education of criminal justice personnel, providers, and the whole citizenry. The women advocated for effective reentry practices.